2021
DOI: 10.1111/ajt.16193
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplant waitlist outcomes in the United States and patient travel distance

Abstract: There is a broad range of patient travel distances to reach a lung transplant hospital in the United States. Whether patient travel distance is associated with waitlist outcomes is unknown. We present a cohort study of patients listed between January 1, 2006 and May 31, 2017 using the Scientific Registry of Transplant Recipients. Travel distance was measured from the patient's permanent zip code to the transplant hospital using shared access signature URL access to Google Maps, and assessed using multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Prior research has evaluated access to a lung transplant center using both geographic distance and rural dwelling, and found that living further away from a lung transplant center decreases the likelihood of lung transplant listing (21). In contrast, a more recent analysis found that a longer travel distance was associated with favorable waitlist outcomes in patients seeking a lung transplant (22). Longer travel distance to clinic has also been associated with an increased risk of death or lung transplant in patients with other fibrotic interstitial lung diseases (23).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has evaluated access to a lung transplant center using both geographic distance and rural dwelling, and found that living further away from a lung transplant center decreases the likelihood of lung transplant listing (21). In contrast, a more recent analysis found that a longer travel distance was associated with favorable waitlist outcomes in patients seeking a lung transplant (22). Longer travel distance to clinic has also been associated with an increased risk of death or lung transplant in patients with other fibrotic interstitial lung diseases (23).…”
Section: Discussionmentioning
confidence: 99%